Charakterystyka sektora finansów samorządowych podkarpacia w procesie absorpcji środków z budżetu Unii Europejskiej - Walenia, Alina (Profile of the Local Government Finance Sector in the Region of Podkarpacie within the Process of Absorbing Funds From the European Union Budget, 2009)
The research results of the empirical material confirm the expertise assessment prepared for the Ministry of Regional Development that the local government units, from the province of Podkarpackie, belong to the provinces of the highest investment potential connected with the programmes subsidised by EU funds. The obligations of the local government sector shall be systematically increasing, and in the second part of the period of 2007-2013, shall exceed the level of 60%. It indicates that finding proper funds in the local government budgets on financing the projects subsidised by EU funds may be the biggest problem in that period. By the end of the period of 2007-2013, the possibilities of launching projects other than those developed within the framework of operational programmes and financed by means of EU funds, shall profoundly decrease. In case of lower, than anticipated, economic growth and therefore the lower income of the incomes of local governments, the problem may appear to be more serious. However, it shall be emphazised that at the beginning of implementing new operational programmes, local governments in the province of Podkarpackie are characterized by the highest ratio of repayment and liabilities service costs to their incomes. This situation may be limiting the possibilities of the increase in further liabilities due to cofinancing of the EU projects.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 349-361